Efekt przetrwania i wyniki inwestycyjne funduszy inwestycyjnych w Polsce - Gabryelczyk, Katarzyna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The purpose of this paper is to examine the impact of the survivorship bias on the performance of Polish mutual fund market in 1999-2004. As a sample we use equity and hybrid funds investing on the local financial market. We calculate the annual unadjusted raw returns as well as risk adjusted returns from a single - index model and then create two portfolios: first, including all the funds which existed at the beginning of 1999 and second, consisting only of the funds which survived until 2004. The estimates are the differences in the returns between those two portfolios. We find that survivorship bias (ranging up to 30 basis points) so far is not essential for the performance of Polish mutual funds. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 1, s. 176-184